Detection of Clarithromycin Resistance in Helicobacter pylori Using MmaxSure™ H. pylori & ClaR Assay - Kim, Ilsoo; Shin, Yu Ri; Kim, Joon Sung; Kim, Byung-Wook; Maeng, Lee-So; Kim, Jung Min (Digestive diseases (Basel), 2024)
Abstract Introduction: Clarithromycin resistance is a crucial factor in the eradication of Helicobacter pylori. This study aimed to evaluate the performance of MmaxSure™ H. pylori & ClaR Assay (MmaxSure™) in the diagnosis and detection of clarithromycin resistance in H. pylori. Methods: Subjects who underwent esophagogastroduodenoscopy between April 2020 and October 2022 were enrolled. The diagnostic performances of MmaxSure™ and dual priming oligonucleotide (DPO)-based multiplex polymerase chain reaction (PCR) were compared with the rapid urease test and culture. Secondary gene sequencing analysis was performed in discordant cases of PCR tests. Results: A total of 156 gastric biopsy samples were analyzed. In H. pylori detection, MmaxSure™ showed a 95.9% sensitivity (95% CI: 90.6–98.6), a 42.7% specificity (95% CI: 26.3–60.7), and a kappa value of 0.457. For the detection of A2143G mutation samples, MmaxSure™ showed a 91.2% sensitivity (95% CI: 76.3–98.1), a 93.4% specificity (95% CI: 87.5–97.1), and a kappa value of 0.804. There were a total of 10 discordant cases compared to gene sequencing in A2143G mutation detection for MmaxSure™. Conclusion: In this study, MmaxSure™ showed comparable diagnostic performance to DPO-PCR in the detection of the H. pylori and A2143G mutation. Further research is needed to confirm the clinical effectiveness of the MmaxSure™ assay in H. pylori eradication.